2006
DOI: 10.1007/s00249-006-0042-1
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cancer cells: magnetic nanoparticles as drug carriers

Abstract: Magnetic drug targeting employing nanoparticles as carriers is a promising cancer treatment avoiding side effects of conventional chemotherapy. We used iron oxide nanoparticles covered by starch derivatives with phosphate groups which bound mitoxantrone as chemotherapeutikum. In this letter we show that a strong magnetic field gradient at the tumour location accumulates the nanoparticles. Electron microscope investigations show that the ferrofluids can be enriched in tumour tissue and tumour cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
195
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(203 citation statements)
references
References 4 publications
2
195
0
2
Order By: Relevance
“…10 Several approaches to improving the selective toxicity of anticancer therapeutics are being pursued presently. [32][33][34] The most commonly used method is Core-shell nanoparticles of Au@silica were synthesized using gold nanoparticles as templates. The porosity of silica shells is regulated by adding 3-aminopropyltrimethoxysilane.…”
Section: Nanoparticles/nanocapsules As Drug Delivery Carriers To Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…10 Several approaches to improving the selective toxicity of anticancer therapeutics are being pursued presently. [32][33][34] The most commonly used method is Core-shell nanoparticles of Au@silica were synthesized using gold nanoparticles as templates. The porosity of silica shells is regulated by adding 3-aminopropyltrimethoxysilane.…”
Section: Nanoparticles/nanocapsules As Drug Delivery Carriers To Cancermentioning
confidence: 99%
“…41,42 Recently, the research of Alexiou et al showed that magnetic drug targeting employing nanoparticles as carriers is a promising system for cancer treatment that does not cause side effects commonly observed in conventional chemotherapy. 32 They used iron oxide nanoparticles covered with starch derivatives with phosphate groups that bind to mitoxantrone, a chemotherapeutical agent. It was demonstrated that a strong-magnetic-field gradient at a tumor site induces the accumulation of nanoparticles, and ferrofluids can become abundant in tumor tissue and tumor cells (Fig.…”
Section: Nanoparticles/nanocapsules As Drug Delivery Carriers To Cancermentioning
confidence: 99%
“…In this context, most studies refer to mitoxantrone (e.g. [1]) or doxorubicin (e.g. [34]) as chemotherapeutic agent.…”
Section: Design Of Mnps As Multifunctional Tools For Magnetic Hyperthmentioning
confidence: 99%
“…Inorganic material allows the production of porous or mesoporous nanoparticles with particle size in range of 50 -300 nm and the pore diameter in the range 5 -50 nm. The porous structure allows high loading capacity for the therapeutic agents and/or tracers, like fluorescein, radioactive compounds or paramagnetic iron (Wiekhorst et al 2006, Alexiou et al 2006a, Alexiou et al 2006b). …”
Section: Nanoparticlesmentioning
confidence: 99%